Comparison of lower-leg muscle activation and establishment of muscle activation patterns during single-leg stance under various instability conditions in healthy active subjects: a cross-sectional study - Mariana Sánchez-Barbadora; Vicente Alepuz-Moner; Noemi Moreno-Segura; Rodrigo Martín-San Agustín (PeerJ)
Background Balance training exercises are essential for treating and preventing a variety of ankle conditions such as sprains, chronic ankle instability, and muscular weakness. This muscle activation could often be increased using unstable devices. The Blackboard is a new configurable selective instability device, that has the potential to focus directly on desired muscles without overloading others through wooden half cylinders slats joined to a board by a tape in different positions. Depending on the position where they are situated, different stability training could be performed. However, its specific muscle activation patterns remain unknown. Methods Surface electromyography was used to measure the activation level of six lower-leg muscles (i.e., soleus, gastrocnemius medialis, gastrocnemius lateralis, tibialis anterior, peroneus longus, and peroneus brevis) in a single-leg stance on the floor and on seven Blackboard configurations. Thirty healthy active subjects participated in the study. Results Multiple differences in muscle activation were observed between conditions and among muscles. Notably, the tibialis anterior and the peroneus showed the greatest differences between conditions and the highest activation levels on the Blackboard. Additionally, forefoot supination and rearfoot eversion configurations induced selective activation of the tibialis anterior and peroneus longus, respectively, highlighting their usefulness for isolating specific muscle contractions.